Integration of Social, Economic, Environmental, and Health Pillars In Sustainable Village Development (Systematic Literature Review Perspective) - Akbar, Bintang Mukhammad Burhanudin; Febrianti , Kemala Citra (Universitas Tidar, 2025)
Sustainable village development requires a holistic approach that integrates four main pillars: social, economic, environmental, and health. A systematic literature review (SLR) based on the PRISMA protocol, conducted on 56 academic documents, successfully identified and mapped the key elements of each pillar. The findings reveal that these four pillars are interwoven and mutually reinforcing within a dynamic framework encompassing participation, equity, resilience, and efficiency. This integration underscores that sustainability depends not only on technical policies but also on local institutional strength, community adaptive capacity, and the principle of inclusiveness. The implication is that village development planning must adopt an integrated and multidisciplinary approach to realize comprehensive, resilient, and sustainable well-being, where the balance among pillars serves as the key to successful transformation toward a better future for rural communities.